Optimization of extraction procedures for nutritional composition from the marine macroalgae Ulva lactuca as a potential cosmetic activity - Darnis, Deny Susanti; Shukor, Muhammad Idham; Mohammad Nor, Normawaty; Aminudin, Nurul Iman; Taher, Muhammad (2023)
In the current study, the ideal extraction method of bioactive compounds from Ulva lactuca was developed and optimised to achieve the maximum yield of extract. The U. lactuca algae were investigated for their vitamin B12 content, carotenoids (beta carotene and fucoxanthin), flavonoid (quercetin), protein and amino acid profiles, and polysaccharides (ulvan). The effects of several extraction parameters, including the solvent-to-solvent ratio, solute-to-solvent ratio, pH, duration of extraction and extraction temperature on the total bioactive compounds of interest content, were analysed through a two-level factorial and central composite design. Other pre- treatment of drying methods (sun-dry, air-dry, oven-dry and freeze-dry) were also applied during the extraction procedure. Results showed that U. lactuca extract was characterised by a high content of ulvan polysaccharides (32.0 %), followed by proteins (27.3 %), carotenoids, flavonoid and vitamin B12. The polysaccharides of ulvan contain L-rhamnose, xylose and glucose. The proteinic fraction analysis indicated the presence of essential amino acids, which represent 42.0% of the total amino acids. The carotenoids profile was represented by the beta carotene, which about 16.0 % of the total carotenoid content, followed by fucoxanthin (11.0 %). Data analysis resulted in optimal extraction condition were noted at pH value 2.5, 85 °C and 2 h for ulvan polysaccharides, 1:25 g/mL, 3 h, 75 °C for protein, 1:31 g/mL, 84 mins, 32 °C for beta carotene, 1:52 g/mL, 87 mins, 34 °C for fucoxanthin, and 1:52 g/mL, 84 mins, 34 °C for quercetin. The highest vitamin B12 content, particularly cyanocobalamin (CN-Cbl), was recovered through the ultrasonic-assisted extraction (UAE) of oven-dried U. lactuca at 3 g:60 mL of solute to solvent and 25:75 % of MeOH to H2O ratios at pH 4. The extraction of CN-Cbl from oven-dried U. lactuca that employed the UAE method has elevated CN-Cbl content recovery compared to other extraction methods.